Covid-19 infection and the host genetic predisposition: does it exist? - Vašků, A (Physiological research, 2020)
Knowledge of genomic interindividual variability could help us to explain why different manifestation of clinical severity of Covid-19 infection as well as modified pharmacogenetic relations can be expected during this pandemic condition.
Keywords: Host-Pathogen Interactions; Peptidyl-Dipeptidase A; Genetic Predisposition to Disease; Angiotensin-Converting Enzyme 2; koronavirové infekce; angiotensin konvertující enzym; pandemie; Betacoronavirus; SARS-CoV-2; angiotensin-konvertující enzym 2; virová pneumonie; lidé; interakce hostitele a patogenu; Humans; Pneumonia, Viral; Pandemics; Coronavirus Infections; genetická predispozice k nemoci; COVID-19